1990
DOI: 10.1159/000185888
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic Responses to 1-Desamino-8-<i>D</i>-Arginine-Vasopressin in Patients with Congenital Nephrogenic Diabetes insipidus

Abstract: Fibrinolytic responses to infusion of 1-desamino-8-.D-arginine-vasopressin (DDAVP) were assessed in 6 males with congenital nephrogenic diabetes insipidus (NDI), 6 carriers of the NDI gene and 6 normal control subjects. Tissue-type plasminogen activator (t-PA) activity and antigen increased significantly in normal subjects, while plasminogen activator inhibitor (PAI) activity decreased. None of these changes were observed in patients with NDI. In 2 female carriers, normal fibrinolytic responses were seen, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…It provokes a marked transient release of von Willebrand factor antigen (vWF:ag), factor VIII coagulant activity and plasminogen activator [6] from endothelial storage sites and exerts a vasodilatory action manifested by facial flushing, a fall in diastolic blood pressure and a rise in pulse rate [5]. Recent studies have demonstrated that patients with NDI do not show these changes in haemodynamic [2], coagulation [2,10] and fibrinolytic [9] parameters after administration of DDAVP. Contrasting with these observations, the study is presented of a 4-year-old boy with severe NDI, who had normal vWF:ag, plasminogen activator and vasodilatory responses to DDAVP.…”
Section: Offprint Requests To: N Knoersmentioning
confidence: 99%
“…It provokes a marked transient release of von Willebrand factor antigen (vWF:ag), factor VIII coagulant activity and plasminogen activator [6] from endothelial storage sites and exerts a vasodilatory action manifested by facial flushing, a fall in diastolic blood pressure and a rise in pulse rate [5]. Recent studies have demonstrated that patients with NDI do not show these changes in haemodynamic [2], coagulation [2,10] and fibrinolytic [9] parameters after administration of DDAVP. Contrasting with these observations, the study is presented of a 4-year-old boy with severe NDI, who had normal vWF:ag, plasminogen activator and vasodilatory responses to DDAVP.…”
Section: Offprint Requests To: N Knoersmentioning
confidence: 99%
“…In addition to mediating antidiuresis, an apparent V2 mediated action of AVP and its V2-specific agonist, l-desamino-8-D-arginine vasopressin (DDAVP), causes release of coagulation and fibrinolytic factors (2] and vasodilation [3]. These extra-Received for publication August 11, 1993 and in revised form January 24,1994 Accepted for publication January 24, 1994 © 1994 by the International Society of Nephrology renal responses are also absent in NDI patients [4][5][6], suggesting that the defect in this disorder might be a dysfunctional or nonfunctional vasopressin V2 receptor.…”
mentioning
confidence: 99%
“…Tissue-type plasminogen activator antigen (tPA:Ag) was measured by an en zyme-linked immunoassay (Innotest, Chromogenix, Zwijndrecht, Belgium). Data were compared with those obtained from 6 NDI patients [3] in whom a V2 receptor gene mutation had been found.…”
Section: Dim Vp Testsmentioning
confidence: 99%
“…In addition to its renal antidiuretic action. DDAVP elicits vasodila tion and an increase of coagulation and fibrinolysis fac tors [2,3]. The exact location of the V2 receptors which mediate these effects is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation